2000
DOI: 10.1046/j.1464-410x.2000.00354.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of a clinical score in the assessment of ambiguous genitalia

Abstract: The masculinization score provides a standardized format to summarize clinical features in newborn infants with ambiguous genitalia. Gender assignment does not solely depend on the appearance of the external genitalia and the nature of internal sexual organs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
157
0
6

Year Published

2005
2005
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(164 citation statements)
references
References 11 publications
1
157
0
6
Order By: Relevance
“…We chose to use the EMS as a method of describing and quantifying the extent of masculinization of the genitalia. 15 Although this is an objective method of assessing genitalia, it is still possible that there may have been some interindividual variation in documenting the score. However, the large data set that was available through the I-DSD registry would have minimized the influence of any error.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We chose to use the EMS as a method of describing and quantifying the extent of masculinization of the genitalia. 15 Although this is an objective method of assessing genitalia, it is still possible that there may have been some interindividual variation in documenting the score. However, the large data set that was available through the I-DSD registry would have minimized the influence of any error.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 454 cases, 382 (84%) also had sufficient information about the external appearance of the genitalia at initial presentation and before any clinical intervention to calculate the external masculinization score (EMS), as previously described. 15 In 7 of 454 (1.5%) cases, sex reassignment at a later stage was reported, and in these cases the initial sex assignment was used for the analysis.…”
Section: Methodsmentioning
confidence: 99%
“…A phenotype of ambiguous genitalia was considered to be present when the patient met the following criteria: 1) manifested genital ambiguity; 2) apparent female genitalia with an enlarged clitoris and labial fusion; and 3) apparent male genitalia with bilateral cryptorchidism, hypospadias or micropenis. 4 The findings relating to the external and internal genitalia were described based on the masculinization score suggested by Ahmed et al 5 and applied by Cools et al 6 With regard to cytogenetic data, the number of metaphases analyzed and their proportions were ascertained in accordance with the 45,X and 46,XY cell lines, in peripheral blood and gonadal tissues.…”
Section: Objectivementioning
confidence: 99%
“…Unfortunately, however, there is no consensus on what would be the best way of handling these patients. 11 Cools et al 6 stated that the masculinization score for the external genitalia that was suggested by Ahmed et al 5 could reflect both gonadal differentiation and the risk of tumors in patients with 45,X/46,XY mosaicism (malignancy risk seems to be inversely related to this score).…”
Section: X/46xy Mosaicism Can Be Detected In Individuals Withmentioning
confidence: 99%
“…AISs in either the complete (CAIS) or partial (PAIS) form represent a relatively common presentation of 46,XY DSD [5–7]. CAIS and PAIS result in complete or partial end organ insensitivity to androgens, respectively.…”
Section: Androgen Insensitivity Syndromes (Aiss)mentioning
confidence: 99%